The relationships among gymnasts' training age, body mass index, balance control, and gymnastics performance - Milosis, D.; Dallas, G.; Kosmidou, E.; Siatras, T. (Science of Gymnastics Journal, 2024)
The aim of the study was the examination of the relationships among gymnasts` training age, body mass index (BMI), balance control during the execution of handstand, standing scale forward, and stork standing in relevé position, and their performance in competition settings. Forty young competitive gymnasts (20 males; age: 12.20 ± 1.98 years, and 20 females; age: 12.33 ± 2.07 years, mean ± SD) participated in this study. A portable digital platform for posturography was used to measure maximal pressure, center of pressure (CoP) sway area, CoP linear distance displacement and CoP velocity. The resulting data were analyzed using an integrated software module (Foot Checker, version 4.0). The results confirm the reliability of the measurements. Strong positive correlations were found between gymnasts' performance in the gymnastics competition, and their training age and BMI, with relationships also identified between performance and variables related to balance control. Regression analysis revealed that gymnasts' training age, BMI, and balance control in performing the assessed gymnastics skills had predictive significance in determining their performance in the competition, taking into account differences between age groups. Despite the limitations of the study, the results represent a valuable contribution to the literature by expanding knowledge about predicting gymnastics performance in competition. Furthermore, the results provide evidence for the identification of talent in gymnasts, offer coaches insights to improve training efficiency, and provide recommendations for future research in this area.